The Influence of Prompt Teacher Feedback in Affecting Student Achievement: Insights from Students’ Perspective at Secondary Level - Saba Farid; Dr. Wajiha Kanwal; Samra Ameer; Taiba Karim (Journal of Management Practices, Humanities and Social Sciences, 2021)
The purpose of the study was to explore and find out the Influence of Prompt teacher feedback in affecting student achievement: insights from students’ perspective at Secondary level. The objective of this study was; 1) To identify different prompt feedback types given by teacher on student performance 2) To explore influence of Prompt teacher feedback in affecting student achievement at secondary level. Prompt feedback of Teachers and academic achievement of the students were considered as the variable of the study. The sample of the study comprises on 260 students at secondary school level. For the research, cross–sectional survey was conducted. Simple convenient sampling method was used for the selection of sample. A modified and self–developed questionnaire was used for study. The data was interpreted by using different tests and statically techniques, like correlation, average mean (M) were used to analyze data. Conclusions were drawn in the light of responses received and on the basis of these conclusion, recommendations were given. It was concluded there is significant relationship between prompt feedback of teachers and academic achievement of students. It is recommended to arrange training sessions for teachers to create awareness among teachers to use the feedback techniques effectively in the class room. This study explains about prompt feedback of teachers increases the achievements of students and provides workable guideline to achieve the objectives of education, by suggesting the improvements in teaching methodology. It might be also helpful to get better quality of education in schools and in turn the attainment of the objectives. It may helpful for the provision of such an environment in an institution which is conducive for good teaching and also stimulates the teaching personnel to achieve the prescribed targets. For the teachers, it might be helpful to understand the student’s psychology and may help them in motivating the students towards right direction.